Urinary apolipoprotein A4 as a biomarker for renal allograft injury in kidney transplant recipients - Youn Kyung Kee; Dong Ho Shin; Jieun Oh; Ji Young Park; Dong Hyun Kim; Kyungjai Ko; Samuel Lee; Hee Jung Jeon (PLoS ONE, 2025)
Chronic renal allograft injury (CRAI) is a major cause of allograft loss in kidney transplant recipients (KTRs). The aim of this study was to evaluate the associations of urinary apolipoprotein A4 (ApoA-IV) levels with renal function and rapid renal function decline in KTRs. This study included 50 KTRs. Proteomic analysis via liquid chromatography‒mass spectrometry and tandem mass spectrometry (LC-MS/MS) was performed to identify potential urinary biomarkers. The SWATH (sequential window acquisition of all theoretical mass spectra) method was used for protein quantification. Urinary ApoA-IV levels were validated by enzyme-linked immunosorbent assay (ELISA). Rapid renal function decline was defined as an estimated glomerular filtration rate (GFR) decrease of >3 mL/min/1.73 m2 per year or initiation of dialysis. The log-transformed urinary ApoA-IV levels measured by ELISA had a significantly inverse correlation with the estimated GFR (r = -0.72, P < 0.001). Moreover, urinary ApoA-IV levels were higher in patients with rapid renal function decline than in those with stable renal function (215.4 ± 181.8 μg/mL vs. 42.5 ± 72.4 μg/mL, P = 0.001). Univariate logistic regression analysis revealed that log-transformed urinary ApoA-IV levels were significantly associated with rapid renal function decline (odds ratio [OR] 6.70, 95% confidence interval [CI] 2.56–22.83; P < 0.001). Multiple logistic regression showed urinary ApoA-IV levels remained a significant risk factor for rapid renal function decline (OR 4.10, 95% CI 1.10–19.55; P = 0.047). ROC curve analysis revealed the area under the curve (AUC) of 0.834 (95% CI 0.722–0.945, P < 0.001) for urinary ApoA-IV levels in predicting rapid renal function decline. Our results suggest that urinary ApoA-IV levels might be a potential biomarker for renal allograft function and could be used as a predictor for rapid renal function decline in KTRs.